Savvy and woke: Gender, digital profile, social media competence, and political participation in gender issues among young Filipino netizens - Dayrit, Julienne Celina Sicat; Albao, Blulean Terosa; Cleofas, Jerome Visperas (Frontiers in Sociology, 2022)
Social media has become a viable platform for political participation in issues related to gender, especially among the youth. Evidence suggests that gender and sexual identities, digital access, and skills foster political participation in social media. This study sought to determine the predictive relationship of gender, digital profile, and social media competence with social media political participation in gender issues (SMPP-GI) among young Filipino netizens through the lenses of social identity theory and resource model of political participation. A total of 1,090 college netizens aged 18–30 years old participated in this cross-sectional study. An online survey was used to collect data. The respondents reported low to moderate levels of SMPP-GI. Females and non-cisheterosexual respondents report higher scores in certain types of SMPP-GI. Respondents using more social media sites have higher levels of latent and counter engagement SMPP-GI. Among the four domains of social media competence, content generation significantly predicted all types of SMPP-GI, while content interpretation and anticipatory reflection were significantly linked with at least one type of engagement.